Investigação sobre aproximações e singularidades nos métodos e processos de projeto em arquitetura e design: da teoria à prática dos escritórios - Garcez, Letícia Vasconcelos Morais (2017)
The similarities among theoretical, technical, practical, and methodological that pervade between Architecture and Design are based on the fact of both using their knowledge to classify and configure design proposals. At the Brazilian Modern Period, it was observed that the dialogue between architects with the Design area occurred as a consequence of thinking about the project in a pluralist way and also due to the lack of professionals graduated in Design course, specifically. One of the reasons that intensifies this situation is on the fact that design teaching courses started late in Brazil, happening only in 1963 with the opening of the ESDI (Escola Superior de Desenho Industrial) with a focus specifically in the Design course and also by offering Design disciplines in the Architecture course at FAU-USP . Therefore, a training of design specialists was driven by the search of answers to industrial, social and economic demands. In this sense, the aim of this study is to approach design methodology questions of Architecture and Design, identifying situations of approximations and singularities on their theoretical and practical contexts. Currently in the Brazilian market there are office groups whose focus can be defined according to three categories: architecture, design, and offices that work with architecture and design in an integrated way. This defines the corpus of this research study which counts on the selection of five offices located in the southeast region of Brazil, having as priority the capitals of São Paulo, Minas Gerais and Rio de Janeiro. Each of the offices was analyzed by comparisons to the methods and project processes used in a way to verify if in the professional practice in Brazil these activities have interactions on the creation methods used in the projects. These are the investigations that surrounds the training of the designer, as well as his design process which will be addressed in this research. The relevance of this study is based on the fact that, although there are specific methodology literature on Architecture project and Design methodologies, both have similarities in their design processes either through the use of the same steps and sequences or by methods used.